A history of classical Malay literature - Fang, Liaw Yock. (Singapore : Institute of Southeast Asian Studies, 2013)
This is a detailed, narrative-based history of Classical Malay Literature. It covers a wide range of Malay texts, including folk literature; the influence of the Indian epics and shadow theatre literature; Panji tales; the transition from Hindu to Muslim literary models; Muslim literature; framed tales; theological literature; historical literature; legal codes; and the dominant forms of poetry, the pantun and syair.The Author describes the background to each of these particular literary periods. He engages in depth with specific texts, their various manuscripts, and their contents.
Keywords: Classical literature -- Malay; Epic literature, Malay -- History and criticism; Javanese literature -- History and criticism; Malay literature -- History and criticism